Influence of Penetration Rate on Full-Flow Penetrometer Resistance in Underconsolidated Clay - Huanhuan Qiao; Xuening Liu; Ruixian Zhou; Huan He; Peng Peng; Zhen Jiang (Journal of Marine Science and Engineering, 2024)
In the past few years, offshore site investigations have extensively utilized full-flow penetrometers like the Ball and T-bar penetrometers to assess penetration resistance and subsequently analyze the strength characteristics of marine clay. The relationship between penetration rate and the measured resistance to penetration and shear strength in clays has been extensively documented through full-flow penetration tests. Although previous studies have shown empirical correlations between undrained shear strength and penetration resistance, the resistance factor utilized in these correlations is typically suggested for cohesive soils that are overconsolidated or normally consolidated, rather than underconsolidated soils. The effects of penetration rate undrained penetration resistances in underconsolidated marine clay are investigated in this study by considering the outcomes of variable rate penetration testing and twitch penetration testing using full-flow penetrometers in laboratory model tests. The discussion focuses on penetration resistances depending on the normalized velocity of the full-flow penetrometers (Ball and T-bar).